(untitled) (LEGAL DIALOGICA, 2025)
The purpose of this study is to determine and analyze the legal regulations on the crime of sexual gratification as a form of abuse of authority and the form of legal responsibility for the crime of sexual gratification. This study uses normative legal research. Where the author conducts research by reviewing legal regulations such as laws, regulations or literature in order to obtain materials in the form of concepts, theories, principles or legal regulations. The sources of legal materials used in this study include primary legal materials, secondary legal materials and tertiary legal materials. The technique of collecting legal materials in this study was carried out by means of library research, and analyzing the collected data requires a method of data processing, the method used must be in accordance with the established approach. The results of this study explain the legal regulations on the crime of sexual gratification as a form of abuse of authority regulated in Law No. 20 of 2001 concerning the Eradication of Criminal Acts of Corruption broadly explains that gratification is the giving of bribes, but referring to Article 12B, not everything that provides benefits can be called gratification, including the giving of sexual services. And the Criminal Responsibility of the perpetrator of the crime of sexual gratification based on Law Number 20 of 2001 concerning corruption, is punishable by imprisonment for a minimum of 1 (one) year and a maximum of 5 (five) years and or a fine of at least Rp. 50,000,000.00 (fifty million rupiah) and a maximum of Rp. 250,000,000.00 (two hundred and fifty million rupiah) for anyone who gives or promises something to a civil servant or state administrator with the intention that the civil servant or state administrator does or does not do something in his position, which is contrary to his obligations. It is better for the legislators to review the provisions on gratification, especially those that have not included sexual gratification as a form of corruption, then the definition of gratification should also be explained more specifically in the explanation of Law Number 20 of 2001 concerning the Eradication of Corruption. The law on sexual gratification should include a form of accountability for such treatment with a higher penalty than the rules stipulated in Article 5 paragraph (1) of Law Number 20 of 2001 so that the perpetrators receive appropriate punishment. Abstrak : Tujuan penelitian ini untuk mengetahui dan menganalisis peraturan hukum terhadap tindak pidana grativikasi seksual sebagai bentuk penyalahgunaan wewenang dan bentuk pertanggung jawaban hukum terhadap tindak pidana grativikasi seksual. Penelitian kali ini menggunakan penelitian hukum normatif. Dimana penulis melakukan penyusunan penelitian dengan mengkaji aturan hukum seperti Undang-undang, peraturan-peraturan ataupun literatur guna untuk mendapatkan bahan berupa konsep, teori, asas ataupun peraturan hukum. Adapun sumber bahan hukum yang digunakan dalam penelitian ini meliputi bahan hukum primer, bahan hukum sekunder dan bahan hukum tersier. Adapun teknik pengumpulan bahan hukum dalam penelitian ini dilakukan dengan cara penelitian kepustakaan (library reseacrch), serta menganalisis data yang terkumpul diperlukan suatu cara pengolahan data, cara yang digunakan harus sesuai dengan pendekatan yang telah ditetapkan.Hasil penelitian ini menjelaskan tentang Peraturan hukum terhadap tindak pidana grativikasi seksual sebagai bentuk penyalahgunaan wewenang di atur dalam Undang-Undang No. 20 Tahun 2001 tentang Pemberantasan Tindak Pidana Korupsi secara garis besar sudah menjelaskan bahwa gratifikasi ialah sebagai pemberian suap, namun merujuk pada pasal 12B, bahwa tidak semua hal yang memberikan manfaat bisa disebut gratifikasi, termasuk pemberian berupa pelayanan seksual. Dan Pertanggung jawaban Pidana pelaku tindak pidana Gratifikasi seksual berdasarkan Undang-Undang Nomor 20 Tahun 2001 tentang tindak pidana korupsi, dipidana dengan pidana penjara paling singkat 1 (satu) tahun dan paling lama 5 (lima) tahun dan atau pidana denda paling sedikit Rp 50.000.000,00 (lima puluh juta rupiah) dan paling banyak Rp 250.000.000,00 (dua ratus lima puluh juta rupiah) setiap orang yang memberi atau menjanjikan sesuatu kepada pegawai negeri atau penyelenggara negara dengan maksud supaya pegawai negeri atau penyelenggara negara tersebut berbuat atau tidak berbuat sesuatu dalam jabatannya, yang bertentangan dengan kewajibannya.Sebaiknya agar pembentuk Undang-Undang untuk meninjau kembali ketentuan tentang gratifikasi khususnya yang belum dicantumkan gratifikasi seksual sebagai salah satu bentuk tindak pidana korupsi, kemudian pengertian gratifikasi juga seharusnya lebih spesifik dijelaskan dalam penjelasan Undang-Undang Nomor 20 Tahun 2001 tentang Pemberantasan Tindak Pidana Korupsi. Seharusnya Undang-Undang tentang gratifikasi seksual tersebut mencantumkan mengenai bentuk pertanggung jawaban atas perlakuannya itu jeratannya lebih tinngi dari aturan yang telah di tentukan pada pasal 5 ayat (1) Undang-Undang Nomor 20 Tahun 2001 agar para pelaku mendapatkan kanjaran yang selayaknya.